Prevalence of HIV-associated neurocognitive disorders in the Multicenter AIDS Cohort Study. (26th January 2016) - Sacktor, Ned; Skolasky, Richard L.; Seaberg, Eric; Munro, Cynthia; Becker, James T.; Martin, Eileen; Ragin, Ann; Levine, Andrew; Miller, Eric
Abstract : Objective: To evaluate the frequency of HIV-associated neurocognitive disorder (HAND) in HIV+ individuals and determine whether the frequency of HAND changed over 4 years of follow-up. Methods: The Multicenter AIDS Cohort Study (MACS) is a prospective study of gay/bisexual men. Beginning in 2007, all MACS participants received a full neuropsychological test battery and functional assessments every 2 years to allow for HAND classification. Results: The frequency of HAND for the 364 HIV+ individuals seen in 2007–2008 was 33% and for the 197 HIV+ individuals seen at all time periods during the 2007–2008, 2009–2010, and 2011–2012 periods were 25%, 25%, and 31%, respectively. The overall frequency of HAND increased from 2009–2010 to 2011–2012 ( p = 0.048). Over the 4-year study, 77% of the 197 HIV+ individuals remained at their same stage, with 13% showing deterioration and 10% showing improvement in HAND stage. Hypercholesterolemia was associated with HAND progression. A diagnosis of asymptomatic neurocognitive impairment was associated with a 2-fold increased risk of symptomatic HAND compared to a diagnosis of normal cognition. Conclusion: HAND remains common in HIV+ individuals. However, for the majority of HIV+ individuals on combination antiretroviral therapy with systemic virologic suppression, the diagnosis of HAND is not a progressive condition over 4 years of follow-up. Future studies should evaluate longitudinal changes in HAND and specific neurocognitive domains over a longer time period.